To the question about value of influence of teeth correction of cylindrical involute oblique-tooth gear on the contact durability - Чернець, М.В.; Ярема, Р.Я. (Problems of Tribology, 2014)
On the base of generalized method of kinetics of contact-friction interaction investigation of influence of teeth correction of cylindrical oblique-tooth involute gear on their tiresome contact durability have been realized. Regularities of change of maximal contact presses as a result of high-altitude and angular hooking correction have been established.